Writing genealogies, constructing men - Punt, J. (Neotestamentica, 2014)
The strong genealogical tenor in the New Testament is uneven with regard to its roles and the value ascribed to it. This article explores along cultural-critical line the increasingly complex interplay between genealogy, masculinity and power with reference to the imperial context. The role of genealogies became ambivalent in imperial times, given challenges to agnatic lineage claims, in a context which both privileged masculinity but also maintained its ambiguity. The persistent yet increasingly complex interplay between genealogies and masculinity forms an interesting context for reading Paul's strained allegory in Galatians 4:21-5:1, particularly with regard to this nexus of genealogy and masculinity.